METHOD FOR PREDICTING PREMATURE LEAVAGE OF AMBITIONAL FLUID WITH DETERMINATION OF SPECIFIC SIGNAL MOLECULES IN BUCCAL EPITHELIA - Kayumova G.M. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
RELEVANCE OF THE PROBLEM Premature rupture of amniotic fluid (PROM) is one of the most common complications of pregnancy (from 8.3 to 19.7%) and is one of the main reasons for the high percentage of surgical delivery , obstetric trauma and neonatal complications. The prognosis for the outcome of childbirth is quite unfavorable when PIOV occurs against the background of a “ripening” or “immature” cervix. The development of non-invasive methods for predicting PIOV in order to reduce perinatal morbidity and mortality is very important. Purpose of the study: verification of key signaling molecules that ensure the integrity of the membranes in the buccal epithelium with the subsequent development of possible biomarkers non- invasive prediction of PIOV.